If an expression within a parenthesis is preceded by the sign +, the parenthesis may be removed without making any change in the signs of the terms of the expression. New School Algebra - Page 11by George Albert Wentworth - 1898Full view - About this book
| Wilbur Fisk Nichols - Arithmetic - 1903 - 328 pages
...sum from 8. What is the result ? If 6 is written 8 — 3 — 2, would you get the same result ? 4. **If an expression within a parenthesis is preceded by the sign —, the parenthesis** can be removed, provided the sign before each term within the parenthesis is changed, the sign + to... | |
| George Albert Wentworth - Algebra - 1906 - 440 pages
...by 10 + (3 - 2). The second process is represented by 10 + 3 - 2. Hence, 10 + (3 - 2) = 10 + 3 - 2. **(2) If we use general symbols in (1) and (2), we have, a + (b + c) = a + b + c, and a + (b** - G) = a + b - c. Hence, The general rule for a parenthesis preceded by + : If an expression within... | |
| Herbert Ellsworth Slaught, Nels Johann Lennes - Algebra - 1912 - 300 pages
...inclosed in a parenthesis with or without change of sign, according as the sign — or + precedes. Eg **a + b — c = a + (b — c) and a — b + c = a — (b — c).** EXERCISES In each of the following, place the last three terms in a parenthesis. 1. x — y + 2 —... | |
| Glenn Moody Hobbs - 1912 - 100 pages
...parenthesis may be removed without making any change in the expression within the parenthesis. (b) When **a parenthesis is preceded by the — sign the parenthesis may be removed** if the sign of every term within the parenthesis be changed. (c) When a number or letter immediately... | |
| George Albert Wentworth - 1913 - 296 pages
...have the following results : aa b + с b — с a — b — с а — b + с We therefore see that **a — (b + c) = a — b — c, and a — (b — c) = a — b + c.** If an expression inclosed within parenthèses is preceded by the negative sign, the parentheses may... | |
| Bernard L. Johnston, Fred Richman - Mathematics - 1997 - 276 pages
...is, (a + b) — b = a and (a - b) + b = a. • Addition and multiplication are associative, that is, **a + (b + c) = (a + b) + c and a . (b . c) = (a . b) . c,** for all a,b,c € R. • There is a zero element, that is, an element 0 in R with the property that... | |
| Christoph Meinel, Thorsten Theobald - Computers - 1998 - 292 pages
...and 0: o + l = l and a-0 = 0, Absorption: a + (a • 6) = a and o • (a + b) — a, Associativity: **a + (b + c) = (a + b) +c and a • (b • c) = (a • b) • c,** DeMorgan's rules: a + 6 = a • b and 0-6 = 0 + 6, Involution: 0 = 0. Figure 3.1. Computation rules... | |
| Charles F. Laywine, Gary L. Mullen - Mathematics - 1998 - 336 pages
...R. then a + be R and a-beR. 2. For all a. be R. a + b = b + a and a . b = b . a. 3. For all ab ce R. **(a + b) + c = a + (b + c) and (a . b) . c = a . (b . c).** 4. For all ab ce R. a . (b + c) = a . b + a . c. 5. There is an additive identity element 0. so a +... | |
| Victor Percy Snaith - Mathematics - 1998 - 180 pages
...are required to satisfy the following axioms: (i) (R, +) is an abelian group, (ii) For all a,b,c £ R **a . (b . c) = (a . b) . c, and a . (b + c) — a . b** + a . c. If, in addition, a . 6 = b . a for all a, 6 € R then R is called a commutative ring. A ring... | |
| |